Cultura, identidade e patrimônio material e imaterial e sua inserção na cultura escolar do ensino médio inovador da rede pública de Laguna – SC - Silva, Ketilin Keli (2016)
The school is an educational institution which provides grants to students in the construction of their knowledge during their school and civic education. It interacts with the essential elements that make up a particular culture and are embedded in all human relationships, for example, language, social relations and religion. This research deals exactly with this relation between the school and local culture, culminating in the formation of a unique and diverse school culture. We focused on the analysis of school culture of two schools in Laguna city, in Santa Catarina state in order to understand how the school culture contributes to civic education. For that, it was necessary to evaluate the cultural elements of the city, whose historical importance made possible the rise of various elements of both the material and immaterial heritage. The research was part of a larger project, implemented in the Centre of Education (OBEDUC). This dissertation presents the results of a research conducted in two schools: Saul Ulyssea and Almirante Lamego, which adopted ProEmi since 2011. The methodology involved field trips in order to evaluate the heritage of these cities, establishing a direct contact with the schools investigated in which were evaluated the pedagogical documents and how they inserted the elements of the local culture in their pedagogical practice. The results indicated that culture, identity and material and immaterial heritage are embedded in school culture of Innovative High Schools, which were surveyed as the curricula and the interdisciplinary projects analyzed.